TRACKING THE CAUSES OF POLITICAL ELITES CORRUPTION - Andina Elok Puri Maharani (Surakarta Law and Society Journal, 2019)
Corruption is a key word in the collapse of people's trust in officials from political parties. This paper tracks the factors that have caused the political elite to commit corruption. The method used in this study is socio legal, by combining legal and political approaches. Based on the discussion, it was concluded that there were 3 (three) things that affected the corruption of the political elite. First, the lack of regulation on political education. Second, the lack of regulation regarding the political recruitment system, and Third, the weak supervision and the Fourth Opportunity. These three things have resulted in corruption that ensnares the political elite, especially those who hold political positions.